Water in the Study of Southeast Asia (KEMANUSIAAN The Asian Journal of Humanities, 2018)
This paper advocates the use of a water perspective in the study of Southeast Asia. Such a perspective, it is argued, is multidimensional and complex, and incorporates an understanding of the physical characteristics of water, the transformations it undergoes through human intervention, and the sociocultural meaning that is applied to it by individual human communities. Moreover, water is a generic term that refers to a variety of types (salt, fresh, brackish, land-water) and forms (oceans, seas, straits, estuaries, rivers, lakes, ponds, reservoirs, canals). By citing examples across the world, this paper proposes the study of the differing combinations of types and forms of water in order to gain a greater precision of its role in Southeast Asia. At the heart of the water approach is the understanding that a body water should be studied as an equal partner to the human community. By examining the dynamic interaction of these two elements, important connectivities and new spatialisations based on water could greatly enhance our understanding of society. The seas, oceans, the littoral, and other forms and types of water are all understudied and deserve renewed attention if we are to find new ways of thinking and learning about Southeast Asia’s past, present and even its future.